Turnaround tools for the teenage brain : helping underperforming students become lifelong learners - Jensen, Eric, 1950-; Snider, Carole, 1941- (Jossey-Bass teacher, 2013)
This book offer teacher-friendly strategies to ensure that all students graduate, become lifelong learners, and ultimately be successful in school and life. Drawing on cutting-edge science, this book reveals core tools to increase student effort, build attitudes, and improve behaviors.